Systematic review of the use of prescription and non-prescription psychotropic drugs and their relation with mental health in university population - Espitia-Cepeda, Catalina; González-Amado, Bárbara; Simó-Algado, Salvador; Villanueva-Blasco, Víctor José (Frontiers in Psychology, 2025)
BackgroundThis systematic review aims to analyze the relationship between prescribed and non-prescribed use of psychotropic drugs and the presence of symptoms of depression, anxiety, stress, suicidal ideation, and suicide in the university population without a clinical disorder diagnosis, considering different types of psychotropic drugs (sedatives, tranquilizers, opioids, sleep aids).MethodsFollowing PRISMA 2020 guidelines, a systematic search was carried out in PubMed/MEDLINE, the Web of Science, Scopus, CINAHL and PsyInfo. Registered in PROSPERO (CRD42023446068). Thirty-four quasi-experimental studies meeting ≥60% MMAT quality were included (assessed using the MMAT) were included. Data extraction considered demographic variables, mental health outcomes, types of psychotropic drugs, and prescription status.ResultsThe findings reveal a significant association between both prescribed and non-prescribed psychotropic drug use and symptoms of psychological distress. Non-prescribed use was more strongly linked to anxiety, stress, and depression, whereas prescribed use was more closely related to suicidal ideation and suicide. Antidepressants, anxiolytics, and opioids were most frequently involved. Women and, in several studies, LGBTQ+ students displayed higher prevalence of psychotropic use in relation to distress.ConclusionThe results emphasize the need for a preventive, contextual, and integral approach to address psychotropic drug use in university settings. Healthy Campus initiatives should reinforce awareness campaigns, promote psychosocial well-being, ensure early detection of psychological distress, and reflect critically on academic structures that may exacerbate emotional difficulties. Further research is needed from an intersectional and multilevel perspective to inform targeted interventions and institutional policy.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023446068, identifier (CRD42023446068).